সম্মুখযুদ্ধ ১৯৭১ : মুক্তিযোদ্ধাদের কলমে - রহমান, মতিউর, ১৯৪৬- (ঢাকা : প্রথমা প্রকাশন, 2015)
Articles on commando operations during the liberation war of 1971, as recounted by the freedom fighters.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Commando operations; Bangladesh -- History -- Revolution, 1971 -- Personal narratives